Facial growth, dentition and function - Proffit, William R.; Quintessence Publishing Co.; Dentaurum (Firm) (Berlin : Quintessence Publishing Group ; [Ispringen, Germany] : Dentaurum, 2000)
This DVD-ROM contains an interactive computer based training (CBT) program to review all the subjects previously featured in the series Dynamics of orthodontics v. 2 to 4. For each volume, 30 interactive questions have been formulated to test and evaluate the user's understanding of key concepts. Immediate feedback is provided, including a detailed explanation of why the user's response is right or wrong and an indication of sections that require further study. Hundreds of images and video clips are shown to reinforce in the user's mind the developmental stages and anatomic structures described in previous volumes in the series.
Facial growth (v. 2a) -- Facial orthopedics (v. 2b) -- Normal development of the dentition (v. 3a) -- Malocclusions and interventions (v. 3b) -- Oral facial functions (v. 4) -- Combination and integration of all DVDs.
Title from disc label
1 guide inserted in container
System requirements: Pentium-class processor with 500 MHz; 256 MB RAM; Windows 2000/XP; video card supporting 1024x768 pixels at 16 bit (high) colour; DVD-ROM drive; 50 MB free hard disk space
Includes complete text and soundtrack in English, Spanish, French, German, Italian, and Portuguese
Keywords: Orthodontics -- Problems and Exercises; Dentition -- Problems and Exercises; Facial Bones -- surgery -- Problems and Exercises; Malocclusion -- therapy -- Problems and Exercises; Maxillofacial Development -- Problems and Exercises; Tooth Eruption -- Problems and Exercises